Development of MSMEs Based on the Pentahelix Model in Supporting Regional Economic Growth in East Java Province - Hafizh Muhammad Aufa; Erika Rahma Novitasari; Indah Prabawati; Firre An Suprapto (Pustaka Digital Indonesia, 2026)
This study aims to analyze the application of the pentahelix model in the development of micro, small, and medium enterprises (MSMEs) to support regional economic growth in East Java Province. MSMEs play an important role in regional economic growth; however, many MSME actors still face various challenges, including limited access to capital, low product innovation, and the limited use of digital technology. This study uses a qualitative approach with a descriptive method based on literature studies and documentation. The data used is secondary data obtained from official government documents, statistical reports, scientific publications, and other relevant sources related to MSME development, regional economic growth, and the concept of pentahelix. Data were collected through documentation and literature review techniques. The analysis was carried out by grouping data based on five pentahelix elements, namely the government, academics, business actors, the community, and the media. The results of the study show that the development of MSMEs in East Java has involved various stakeholders, but the synergy between actors has not run optimally. The government plays a role in providing empowerment policies and programs, academics contribute through research and mentoring, business actors play a role in innovation and market development, the community supports socio-economic networks, while the media plays a role in the promotion and dissemination of information. The main obstacles that are still faced are weak coordination, the lack of integration of inter-sector programs, and the limited use of digital technology by some MSME actors. Therefore, strengthening pentahelix collaboration is needed so that the development of MSMEs can run more effectively, sustainably, and be able to make a greater contribution to regional economic growth